Drill of the Absolute Torque and their Effect on Some Biochemical Variables for Some Stages of 60-Meter Hurdle-Runners - Mazin Anhair Lami (Journal of Global Pharma Technology, 2018)
The need to apply special resistance exercises to athletics has become particularly strong and the indices are falling apart at every international tradition pattern of power workouts, according to the parts. Different which moves rotational movements especially running hurdles, so this search came to muscle totals operating for a 60-meter hurdles in accordance with the movements specify within the axis of the rotation of these parts, the angular kinetic work of these joints in order to achieve the condition of the runner’s power in such an efficiency to increase his muscle efficiency. The search applied to a group of runners who ran 60 roadblocks in Iraq and researchers prepared skill-based exercises with weight-added resistors to body parts according to the percentages of these parts, to develop kinetic variables. For some stages, 60 meters of hurdles were run and the exercises were applied for eight weeks, three training modules per week. The results have shown the evolution of these variables of force and speed and angles during the run, between the hurdles and the hurdle step for group research.Keywords: Absolute torque, Relative momentum and unbalanced Power.